Photobiomodulation for the management of pain and paresthesia following surgical removal of mini orthodontic screw in the maxillary sinus. - Herrera-Plasencia , Paul Martín (2024)
Introduction: Mini screws are devices used to optimize anchorage in orthodontics, and are fixed in the bone structure. Case of report: We present the case of a patient who came to the oral and maxillofacial surgery office due to the accidental introduction of a mini orthodontic screw into the maxillary sinus; a tomographic evaluation was requested, determining the thickening of the Schneider membrane and the presence of the foreign body inside it. The Caldwell-Luc surgical technique was performed and the mini screw was located and removed. Subsequent complications were pain on touch and paresthesia; a laser therapy with photobiomodulation was performed, and both pain and paresthesia were resolved. Conclusion: One year after surgery, the patient was asymptomatic and without paresthesia, the control tomography verified absence of Schneider's membrane thickening and permeable anatomical repairs of the left maxillary sinus.